2021
DOI: 10.1186/s13018-021-02749-z
|View full text |Cite
|
Sign up to set email alerts
|

The risk for complications and reoperations with the use of mega prostheses in bone reconstructions

Abstract: Background Despite a relatively high risk for complications and reoperations, mega prostheses are considered a useful method for reconstruction of bone defects after tumour resections. The total number of reoperations has not previously been described, and little is known about the complication rate of mega prostheses used for other indications than primary bone tumours. Questions/purposes The current retrospective observational study aimed to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Eleven of the included studies in this review were retrospective in nature, presenting outcomes related to PJI after tumor resection and megaprosthetic reconstruction [11,12,14,15,[17][18][19][20][21][22][23]. Two studies specifically compared results between patients with silver-coated and titanium prostheses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of the included studies in this review were retrospective in nature, presenting outcomes related to PJI after tumor resection and megaprosthetic reconstruction [11,12,14,15,[17][18][19][20][21][22][23]. Two studies specifically compared results between patients with silver-coated and titanium prostheses.…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of any adjuvant therapy for the treatment of malignancy was shown to increase the possibility of infection [14,18]; specifically, four studies reported that radiotherapy was a significant risk factor for PJI [2,12,13,19]. Chemotherapy has been associated with a higher risk for PJI in one study [19], while in others it did not seem to be associated with increased rates of infection [2,11,12,15,20,22]. Tumor location and reconstruction in the tibia [2,14,17] and the pelvis [2,17] notably increased the risk of PJI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Megaprostheses are modular endoprostheses, consisting of several different components in promptly available sets, which can be assembled in different combinations to fit the specific skeletal defect allowing limb sparing. The rational use of this system aims to restore the function of limbs as quickly as possible in order to improve quality of life, minimize the morbidity associated with the surgical procedure and hospitalization, and continue oncologic therapies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1] MP is a widely accepted technique for joint reconstruction after the resection of bone and soft tissue tumors, but it has a relatively high complication rate. [2] Among the various complications, postoperative infection is the most frequent and difficult problem. [3] In fact, the incidence of periprosthetic joint infections (PJIs) has been reported as 0.25% to 2.0% for hip and knee joint revisions [4] and as 4% to 20% after tumor resection.…”
Section: Introductionmentioning
confidence: 99%